2017
DOI: 10.1007/s10211-017-0265-4
|View full text |Cite
|
Sign up to set email alerts
|

Immune challenge of female great tits at nests affects provisioning and body conditions of their offspring

Abstract: The trade-off between animal’s parental reproductive effort and survival is still poorly understood. Parental allocation between the workload during breeding attempts and the parents’ own body conditions can be assessed through the offspring quality. Here, I questioned whether the immune responsiveness of female great tits may be considered as a mediator of this trade-off. Specifically, I tested whether (1) the parental reproductive effort decreases, (2) the food composition provided to chicks changes, and (3)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 74 publications
0
12
0
Order By: Relevance
“…Humoral immunity of wild birds has been influenced by climate changes, migration, season, reproductive performance, and age. These factors have emerged as interesting areas of study for wild avian species ( Kilpimaa et al., 2007 ; Martyka et al., 2011 ; Grzedzicka, 2017 ). Other poultry species were totally assigned in 15 publications that included studying SRBC in ducks (5 studies), pheasants (3 studies), dwarf chickens, geese, guinea fowl, ostrich, partridges, and pigeons (each with 1 study).…”
Section: Resultsmentioning
confidence: 99%
“…Humoral immunity of wild birds has been influenced by climate changes, migration, season, reproductive performance, and age. These factors have emerged as interesting areas of study for wild avian species ( Kilpimaa et al., 2007 ; Martyka et al., 2011 ; Grzedzicka, 2017 ). Other poultry species were totally assigned in 15 publications that included studying SRBC in ducks (5 studies), pheasants (3 studies), dwarf chickens, geese, guinea fowl, ostrich, partridges, and pigeons (each with 1 study).…”
Section: Resultsmentioning
confidence: 99%
“…The nest boxes were hung on trees approximately 2 m above the ground, with distance of 40–50 m between trees with nest boxes. Habitat in the research area is a deciduous forest dominated by an oak‐hornbeam plant community (see Grzędzicka, for a detailed habitat description). The most common bird species occupying those nest boxes was the great tit, Parus major (about 70 successful nests per year), while the second numerous one was the Eurasian blue tit, Cyanistes caeruleus (about 35–40 successful nests per year).…”
Section: Methodsmentioning
confidence: 99%
“…Nine days after hatching, food items were collected from the nests. Soft collars made of velcros (Velcro, textile standard, black) intended for clothes were fastened around the necks of all nestlings per nest for 2 hr in the period from dawn until 12 am (see Grzędzicka, for details of this method). Caterpillars and other invertebrates (mainly spiders) were collected from the bills of young birds using tweezers.…”
Section: Methodsmentioning
confidence: 99%
“…food access. For example, some previous studies found a direct relationship among the food intake, body mass and PHA response (Yellow-legged Gulls Larus cachinnans: Alonso-Alvarez and Tella 2001; Great Tits: Grzędzicka 2017). However, studies describing the importance of environmental factors for the maternal investment in offspring immunity are lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Exposure of female Tree Swallows Tachycineta bicolor to sheep red blood cells (SRBC) had no effect on the cell-mediated immunity in their broods (Lozano and Ydenberg 2002). In Great Tits Parus major, the PHA responses of nestlings of SRBC-challenged mothers were lower than in control chicks (Grzędzicka 2017).…”
Section: Introductionmentioning
confidence: 99%